Cured product of addition curing type silicone rubber composition and optical parts for ultraviolet irradiation device
By adjusting the formulation and process conditions of the silicone rubber resin, the problem of poor durability of resin under deep ultraviolet light irradiation is solved, and high-light transmissivity and low degradation are achieved, which is suitable for light distribution control of ultraviolet light irradiation equipment.
Patent Information
- Application Number
- JP2025004101
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
In the prior art, under deep ultraviolet light irradiation, the durability of silicone rubber resin is poor, resulting in a decrease in light transmission mittance and the ultraviolet light distribution cannot be effectively controlled.
By adjusting the formulation and process conditions of the silicone rubber resin, the stability of the resin under deep ultraviolet light is ensured. Specific measures include controlling the concentration of vinyl group and hydrosilyl group in the resin, and adjusting the heat treatment conditions of the resin to obtain higher light transmission and durability.
The low degradation and high durability of silicone rubber resin under deep ultraviolet light irradiation are achieved, ensuring the stability of light transmission mittance and effectively controlling the ultraviolet light distribution.
Smart Images

Figure 0007665120000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cured product of an addition-curing silicone rubber composition and an optical part for an ultraviolet irradiation device. [Background technology]
[0002] Ultraviolet irradiation devices using light sources such as LEDs that emit deep ultraviolet rays with wavelengths of 300 nm or less are used in various devices for disinfection, sterilization, purification, etc. In such devices, a light flux control member is used to expand the light emitted from the light source to a distribution suitable for the irradiation target.
[0003] Polymethyl methacrylate (PMMA) and polycarbonate (PC) are known as general-purpose molding materials used for optical applications. However, these resin materials are poorly transparent to ultraviolet light, so they cannot be used as molding materials for the light flux control members described above. For this reason, expensive, difficult-to-process materials such as quartz and fluororesin are used instead.
[0004] In response to this, addition-curing silicone rubber compositions have been studied as molding materials with ultraviolet light transmittance. For example, Patent Document 1 discloses the use of a cured product of an addition-curing silicone rubber composition containing an organopolysiloxane having an alkenyl group bonded to a silicon atom, an organohydrogenpolysiloxane having a hydrogen atom bonded to a silicon atom, and a catalyst as an optical part. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-31543 Summary of the Invention [Problem to be solved by the invention]
[0006] However, according to the study by the present inventors, it has become clear that the cured product obtained by Patent Document 1 is easily deteriorated by irradiation with ultraviolet light, particularly deep ultraviolet light, and has low durability. Therefore, when the cured product is irradiated with ultraviolet light for a certain period of time, the transmittance decreases, and the desired light distribution cannot be obtained, which is a problem.
[0007] An object of the present invention is to provide a cured product of a silicone rubber composition that is durable and undergoes little deterioration when exposed to deep ultraviolet light, and an optical part for an ultraviolet irradiation device that uses the same. [Means for solving the problem]
[0008] The present invention relates to the following cured product and optical component for an ultraviolet irradiation device.
[0009] [1] A cured product of an addition-curing silicone rubber composition, 13 A cured product, in which in a C-MAS-NMR spectrum, the ratio of the area of peak B appearing at 18.0 to 18.5 ppm to the total area of peak A appearing at 9.0 to 10.0 ppm is 31% or more and 68% or less. [2] A cured product of an addition curing type silicone rubber composition, which has an absorption spectrum of 2120 to 2180 cm in an ATR-FTIR spectrum. -1 The concentration of hydrosilyl groups in the cured product calculated from a peak derived from hydrosilyl groups appearing in the cured product is 0.20 mmol / g or more and 0.54 mmol / g or less. [3] In the ATR-FTIR absorption spectrum, the peak at 1630-1670 cm -1 The cured product according to [1] or [2], wherein a peak derived from a vinyl group appearing in the [4] The addition-curable silicone rubber composition comprises (A) an organopolysiloxane having an average composition represented by formula (1), 1 a SiO (4-a) / 2 (In the formula, R 1is an alkenyl group, an alkyl group having 1 to 6 carbon atoms, a fluorinated alkyl group having 1 to 6 carbon atoms, an aryl group, or a cycloalkyl group having 5 to 12 carbon atoms, and R 1 at least two of which are alkenyl groups, and a is a positive number of 1.95 to 2.05), (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in each molecule, and (C) a curing catalyst. [5] An optical part for an ultraviolet irradiation device, comprising the cured product according to any one of [1] to [4]. Effect of the Invention
[0010] According to the present invention, it is possible to provide a cured product of a silicone rubber composition that is less susceptible to deterioration due to irradiation with deep ultraviolet light and has durability, and an optical part for an ultraviolet irradiation device using the same. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram showing an ultraviolet irradiation device according to the present embodiment. [Diagram 2] FIG. 2A is a plan view of an ultraviolet irradiation device according to another embodiment, and FIG. 2B is a cross-sectional view taken along line BB in FIG. 2A. [Diagram 3] FIG. 3 is a diagram showing a schematic configuration of the device used in the ultraviolet irradiation test. [Figure 4] FIG. 4 shows the 13C-MAS-NMR spectrum of Example 4. [Diagram 5] 5A and 5B are diagrams showing ATR-FTIR absorption spectra of Examples 1 to 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments, and can be practiced with various modifications within the scope of the gist of the present invention. In addition, in this specification, a numerical range expressed using "to" means a range including the numerical values before and after "to" as the lower and upper limits.
[0013] 1.Cured product The cured product of this embodiment is a cured product of an addition curing type silicone rubber composition. The addition curing type silicone rubber composition contains an organopolysiloxane component having an unsaturated bond (e.g., a -Si-CH=CH2 structure) and an organohydrogenpolysiloxane component having a hydrosilyl group (-SiH), and when heated in the presence of a catalyst, these components undergo a hydrosilylation reaction and are cured.
[0014] [ 13 C-MAS-NMR] The present inventors have found that even in cured products obtained from the same material, the susceptibility to degradation by deep ultraviolet rays varies depending on the degree of thermal history of the material during the curing process and after curing until the product is obtained. Further analysis of multiple cured products with different susceptibility to degradation by deep ultraviolet rays revealed the following: 13 It was revealed that a cured product in which the ratio of the area of peak B appearing at 9.0 to 10.0 ppm to the sum of the area of peak A appearing at 18.0 to 18.5 ppm and the area of peak B appearing at 9.0 to 10.0 ppm in a C-MAS-NMR spectrum is equal to or less than a specified value is less susceptible to degradation by deep ultraviolet light (see FIG. 4 described later).
[0015] The reason for this is not clear, but is presumed to be as follows. In the addition curing reaction of silicone rubber compositions, for example, an organopolysiloxane component having a -Si-CH=CH2 structure undergoes a hydrosilylation reaction with an organohydrogenpolysiloxane component having a hydrosilyl group (-Si-H) to produce a crosslinked structure (see (1) and (2) below). Meanwhile, a portion of the organopolysiloxane component having a -Si-CH=CH2 structure is thought to remain unreacted (see (3) below). [ka]
[0016] 13 In the C-MAS-NMR spectrum, peak A appearing at 18.0 to 18.5 ppm is derived from crosslinked structure (2), which is stable against deep ultraviolet light (see peak A in FIG. 4 described later). On the other hand, peak B appearing at 9.0 to 10.0 ppm is derived from crosslinked structure (1), which is unstable against deep ultraviolet light (see peak B in FIG. 4 described later). In other words, when the ratio of the area of peak B is a predetermined value or less, the amount of unstable crosslinked structure (1) in the cured product is relatively small, and the amount of stable crosslinked structure (2) is relatively large, so that it is considered that deterioration against deep ultraviolet light can be suppressed.
[0017] That is, the cured product is 13 In a C-MAS-NMR spectrum, the ratio of the area of peak B appearing at 9.0 to 10.0 ppm to the sum of the area of peak A appearing at 18.0 to 18.5 ppm and the area of peak B appearing at 9.0 to 10.0 ppm (hereinafter also referred to as the "area ratio of peak B") is 31% or more and 68% or less.
[0018] When the area ratio of peak B of the cured product is 68% or less, as described above, the unstable crosslinked structure (1) is relatively small and the stable crosslinked structure (2) is relatively large, so that the cured product is less likely to deteriorate due to deep ultraviolet rays. The area ratio of peak B is preferably 35% or more and 65% or less.
[0019] Hardened product 13C-MAS-NMR measurement can be performed by the following procedure. First, the cured product to be measured is cut into 0.5 to 1.0 mm square samples. Next, the sample is filled in the center of a solid-state NMR sample tube and subjected to a solid-state NMR measurement device (e.g., VNMRS-400 manufactured by Varian) under the following conditions: 13 Perform C-MAS-NMR measurement. (Measurement conditions) Observation kernel: 13 C Observation frequency: 100.5MHz Measurement method: DDMAS Reference material: Adamantane Pulse width: 2.7μsec Waiting time: 15sec Number of times: 5800 Rotation frequency (MAS rotation speed): 15kHz Sample temperature: 23℃
[0020] NMR data processing can be performed using commercially available NMR data processing software (e.g., Delta v6.0 manufactured by JEOL, etc.). For example, baseline correction can be performed using an automatic baseline correction function of commercially available NMR data processing software (e.g., the "Base Correct" function of Delta v6.0 manufactured by JEOL).
[0021] 13 The area ratio of peak B in the C-MAS-NMR spectrum can be adjusted by the thermal history of the cured product, particularly the heating temperature and heating time during the curing reaction. Specifically, the area ratio of peak B increases with an increase in the thermal history. Therefore, the area ratio of peak B can be reduced by reducing the thermal history by lowering the heating temperature or shortening the heating time within a range that does not interfere with curing.
[0022] [ATR-FTIR] As a result of further analysis, the present inventors found that the ATR-FTIR absorption spectrum of the cured product had a peak at 2120 to 2180 cm -1It was also revealed that cured products with a hydrosilyl group concentration of 0.20 mmol / g or more and 0.54 mmol / g or less, calculated from the peaks derived from hydrosilyl groups that appear in the cured product, also showed little degradation due to ultraviolet rays.
[0023] The reason for this is not clear, but is presumed to be as follows. According to the study by the present inventors, the concentration of hydrosilyl groups in the cured product decreases with increasing thermal history. In other words, when the concentration of hydrosilyl groups is 0.20 mmol / g or more, the thermal history is not too large, so that it is difficult to generate an unstable crosslinked structure (1) and it is difficult to cause deterioration due to deep ultraviolet rays. From the same viewpoint, the concentration of hydrosilyl groups in the cured product is preferably 0.24 mmol / g or more, more preferably 0.26 mmol / g or more.
[0024] In addition, the organopolysiloxane component having an unsaturated bond and the organohydrogenpolysiloxane component having a hydrosilyl group react at a ratio of 1:1. Therefore, when the charge ratio of the organopolysiloxane component having an unsaturated bond and the organohydrogenpolysiloxane component having a hydrosilyl group is 1:1, if the concentration of the hydrosilyl group in the cured product is 0.54 mmol / g or less, the concentration of the vinyl group derived from the organopolysiloxane component having an unsaturated bond is correspondingly low, so that yellowing is unlikely to occur and deterioration due to deep ultraviolet rays can be reduced. From the same viewpoint, the concentration of the hydrosilyl group in the cured product is preferably 0.50 mmol / g or less (see FIG. 5B described later).
[0025] In order to reduce yellowing and deterioration when irradiated with deep ultraviolet light, it is preferable that the concentration of unreacted vinyl groups (above (3)) in the cured product is low. Specifically, in the ATR-FTIR absorption spectrum of the cured product, -1It is preferable that the peak derived from the vinyl group appearing in the spectrum is undetectable (see FIG. 5A described later). The term "undetectable peak" means that the spectrum is broadened and cannot be detected as a peak (the concentration of the vinyl group calculated from the peak is below the lower detection limit of the measuring device).
[0026] The concentration of unreacted vinyl groups in the cured product can also be estimated from the concentration of unreacted hydrosilyl groups in the cured product. As described above, the ratio of the organopolysiloxane component having an unsaturated bond to the organohydrogenpolysiloxane component having a hydrosilyl group is usually about 1:1, and the two react at a ratio of 1:1.
[0027] Attenuated Total Reflection (ATR) infrared spectroscopy (ATR-FTIR) of the cured product can be carried out according to the following procedure. (Measurement conditions) Equipment: Fourier transform infrared spectrophotometer (e.g. Agilent Cary 620 FTIR manufactured by Agilent Technologies) Measurement method: Microscopic ATR method ATR prism: Germanium (spherical) refractive index 4.0 Incident angle: 30° Measurement area: 650~4000cm -1 Detector: MCT, High Sensitivity 100μm Reflection count: 1 Resolution: 4cm -1 Number of times accumulated: 128 times
[0028] The background measurement is performed in the same way, except that the sample is not brought into contact with the prism. In the ATR method, the intensity of the absorption spectrum obtained by the measurement changes depending on the degree of contact between the sample and the ATR prism, so the measurement is performed so that the maximum peak intensity is 0.33 to 0.34.
[0029] In the resulting absorption spectrum, -1 and 926cm -1are defined as the left and right starting points of the baseline, respectively, and 1013 cm -1 The height of the peak due to the Si-O bond near h ref Also, 2193 cm -1 and 2080cm -1 are defined as the left and right starting points of the baseline, respectively, and 2138 cm -1 The peak height h due to the hydrosilyl group in the vicinity SiH These values are then substituted into the following formula to calculate the concentration of hydrosilyl groups (SiH concentration). SiH concentration [mmol / g] = 30.2 × h SiH / h ref +0.021 The above formula is a calibration curve obtained from the absorption spectrum when ATR-FTIR is measured for a sample with a known SiH concentration.
[0030] Similarly to the above, the concentrations of vinyl groups and hydrosilyl groups in the cured product can be adjusted by the thermal history, particularly the curing temperature and curing time during the curing reaction, etc. For example, the concentration of hydrosilyl groups and the concentration of vinyl groups can be decreased by increasing the thermal history by increasing the heating temperature or the heating time.
[0031] In this way, the hardened 13 The area ratio of peak B in the C-MAS-NMR spectrum and the concentration of vinyl groups and hydrosilyl groups measured from the ATR-FTIR absorption spectrum can be adjusted by the thermal history of the cured product. Therefore, the silicone rubber composition is not particularly limited as long as it undergoes an addition curing reaction, and any known silicone rubber composition can be used. The components of the silicone rubber composition will be specifically described below.
[0032] [Silicone rubber composition] The silicone rubber composition contains (A) an organopolysiloxane having at least two alkenyl groups per molecule, (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms per molecule, and (C) a curing catalyst.
[0033] <Component (A)> Component (A) is an organopolysiloxane having at least two alkenyl groups, preferably silicon-bonded alkenyl groups, per molecule, and functions as the base component of the silicone rubber composition. The average composition of this organopolysiloxane is represented by formula (1). Formula (1): R 1 a SiO (4-a) / 2
[0034] R in Equation (1) 1 is an alkenyl group, an alkyl group having 1 to 6 carbon atoms, a fluorinated alkyl group having 1 to 6 carbon atoms, an aryl group, or a cycloalkyl group having 5 to 12 carbon atoms. 1 At least two of these R are alkenyl groups. 1 is a substituent that does not absorb UVC light.
[0035] Examples of the alkenyl group include a vinyl group, an allyl group, a butenyl group, a pentenyl group, and a hexenyl group, and the vinyl group is preferred. The alkenyl group may be present at the end of the molecular chain or in a side chain.
[0036] Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethylene group, a propyl group, and a butyl group. Examples of the fluorinated alkyl group having 1 to 6 carbon atoms include groups in which a part of these alkyl groups is substituted with a fluorine atom. The aryl group is preferably an aryl group having 6 to 12 carbon atoms, and examples thereof include a phenyl group and a tolyl group. By appropriately adjusting the concentration of the aryl group, it is possible to further suppress the absorption of deep ultraviolet light. Examples of the cycloalkyl group having 5 to 12 carbon atoms include a cyclohexyl group and a cyclohexenyl group.
[0037] In formula (1), a is a positive number from 1.95 to 2.05.
[0038] The organopolysiloxane represented by formula (1) is preferably linear, and may partially contain a branched structure. That is, the organopolysiloxane represented by formula (1) preferably contains diorganosiloxane units (D units) as a main component. Specifically, the content of D units is preferably 90 mol % or more based on the total constitutional units (total siloxane units) of the organopolysiloxane. The type and amount of siloxane units are as follows: 29 It can be identified by analysis using Si-NMR. The organopolysiloxane represented by formula (1) is preferably liquid at 25°C.
[0039] The organopolysiloxane represented by formula (1) is preferably a linear organopolysiloxane whose main chain contains diorganosiloxane units (D units) as a main component and whose molecular chain is terminated at both ends with triorganosiloxane units (M units). 1 Among these, the groups other than the alkenyl group preferably contain a methyl group. The alkenyl group is preferably a vinyl group.
[0040] The alkenyl group content of the organopolysiloxane represented by formula (1) is not particularly limited, but is preferably 0.02 mmol / g or more, more preferably 0.05 mmol / g or more. When the alkenyl group content is 0.02 mmol / g or more, the crosslink density of the cured product is higher, so that the hardness is easier to increase. The upper limit of the alkenyl group content is preferably less than 1.0 mmol / g, more preferably less than 0.8 mmol / g. When the alkenyl group content is less than 1.0 mmol / g, the crosslink density of the cured product is unlikely to be excessively high, so that the breaking elongation of the cured product is unlikely to be impaired, and the toughness is unlikely to be impaired. As long as the alkenyl group content of the mixture is within the above range, two or more organopolysiloxanes having different alkenyl group contents may be used in combination.
[0041] The content of component (A) is preferably 40 to 98 mass % and more preferably 50 to 95 mass % of the silicone rubber composition. When the content of component (A) is at a certain level or more, it is easier to obtain a cured product with better moldability and appropriate hardness.
[0042] <(B) component> Component (B) is an organohydrogenpolysiloxane that has at least two hydrogen atoms bonded to silicon atoms (-SiH) in each molecule, and can function as a crosslinking agent for component (A).
[0043] The organohydrogenpolysiloxane may be linear or branched. The degree of polymerization of the organohydrogenpolysiloxane is not particularly limited, but is, for example, 2 to 300, and preferably 4 to 200. The hydrogen atom bonded to the silicon atom may be at the end of the molecular chain or in a side chain.
[0044] The organic group bonded to the silicon atom is an alkyl group having 1 to 6 carbon atoms or a cycloalkyl group having 5 to 12 carbon atoms. Among these, an alkyl group having 1 to 6 carbon atoms is preferred, and a methyl group is more preferred.
[0045] The content of hydrogen atoms bonded to silicon atoms in the organohydrogenpolysiloxane is not particularly limited as long as it is sufficient to react with the alkenyl groups of the component (A), but it is preferably 0.1 mmol / g to 20 mmol / g.
[0046] Examples of organohydrogenpolysiloxanes include diorganopolysiloxanes blocked with dimethylhydrogensilyl groups, copolymers containing dimethylsiloxane units, methylhydrogensiloxane units, and terminal trimethylsiloxy groups, copolymers containing dimethylhydrogensiloxane units and SiO 4 / 2units (Q units), 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane, 1-propyl-3,5,7-trihydrogen-1,3,5,7-tetramethylcyclotetrasiloxane, 1,5-dihydrogen-3,7-dihexyl-1,3,5,7-tetramethylcyclotetrasiloxane, and the like.
[0047] The content of the (B) component is not particularly limited as long as it is within a range that can sufficiently crosslink the (A) component, but the number of moles of the hydrosilyl groups in the (B) component is preferably 0.8 to 5 moles, and more preferably 1 to 3 moles, per mole of the alkenyl groups in the (A) component.
[0048] <(C) component> Component (C) is a catalyst for promoting the hydrosilylation reaction between components (A) and (B). Known hydrosilylation reaction catalysts can be used as such a catalyst. Examples of such catalysts include platinum black, platinic chloride, chloroplatinic acid, reaction products of chloroplatinic acid and monohydric alcohols, complexes of chloroplatinic acid and olefins, palladium-based catalysts, and rhodium-based catalysts.
[0049] The content of component (C) is not particularly limited, but for example, the amount of platinum atoms is preferably 0.5 ppm by mass or more and 300 ppm by mass or less, more preferably 1 ppm by mass or more and 200 ppm by mass or less, and even more preferably 2 ppm by mass or more and 100 ppm by mass or less, per 100 parts by mass of the combined total of components (A) and (B).
[0050] <Other ingredients> The silicone rubber composition may further contain other components in addition to those described above, as necessary. Examples of the other components include an alkenyl-containing organopolysiloxane other than the component (A) (e.g., silicone resin (D)), silica particles (E), and a hydrosilylation reaction inhibitor (F).
[0051] ((D) component) (D) component is R2 SiO 3 / 2 Units (T units) and SiO 4 / 2 It is a silicone resin that contains at least one of the units (Q units) and has at least two alkenyl groups in one molecule. 2 is a monovalent hydrocarbon group having 1 to 6 carbon atoms. Such a silicone resin has a three-dimensional network structure, which can increase the hardness of the cured product of the silicone rubber composition. 2 At least two of the T and Q groups are preferably alkenyl groups. The total amount of T units and Q units may be 50 mol % or more based on the total structural units of the silicone resin.
[0052] Examples of the monovalent hydrocarbon group having 1 to 6 carbon atoms include an alkyl group, a cyclohexyl group, a cyclohexenyl group, and an alkenyl group. The alkyl group having 1 to 6 carbon atoms is preferably a methyl group. The alkenyl group is preferably a vinyl group.
[0053] Examples of silicone resins include R 2 3SiO 1 / 2 Units (M units) and SiO 4 / 2 Silicone resin containing units (Q units), R 2 SiO 3 / 2 Units (T units) and SiO 4 / 2 Silicone resin containing units (Q units), R 2 SiO 3 / 2 These include silicone resins composed of units (T units). Specific examples include copolymers of vinyldimethylsiloxy groups and Q units, copolymers of vinyldimethylsiloxy groups, trimethylsiloxy groups and Q units, copolymers of vinyldimethylsiloxy groups, dimethylsiloxane and Q units, and copolymers of trimethylsiloxy groups, vinylmethylsiloxane and Q units.
[0054] The content of the component (D) can be, for example, 5 to 50 parts by mass per 100 parts by mass of the component (A).
[0055] ((E) component) Silica particles (E) can be added from the viewpoint of increasing the ultraviolet ray diffusion effect of the cured product and imparting sufficient tear strength and strength to the cured product. The type of silica particles (E) is not particularly limited, but from the viewpoint of not hindering the function of the catalyst of component (C), gel method silica or fumed silica is preferred, and hydrophobically treated fumed silica particles are more preferred. The hydrophobically treated silica particles can be silica particles surface-treated with a silane coupling agent, a silazane compound, or a low molecular weight siloxane compound having a hydrophobic group.
[0056] The average primary particle diameter of the silica particles (E) is preferably 5 to 300 nm, more preferably 5 to 100 nm. When the average primary particle diameter is 5 nm or more, the ultraviolet ray diffusion effect is improved and the effect of improving the mechanical strength is easily obtained. When the average primary particle diameter is 300 nm or less, the decrease in the ultraviolet ray transmittance can be further suppressed.
[0057] The content of the component (E) is preferably 1 to 20 parts by mass, and more preferably 2 to 10 parts by mass, per 100 parts by mass of the component (A).
[0058] (Component (F)) The silicone rubber composition may further contain a hydrosilylation reaction inhibitor ('F) from the viewpoint of ensuring pot life. Examples of the hydrosilylation reaction inhibitor include polyfunctional alkenyl compounds such as 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, and acetylene alcohol derivatives such as 2-methyl-3-butyn-2-ol, 3-methyl-1-butyn-3-ol, and 3-methyl-1-pentyn-3-ol.
[0059] The content of the component (F) is preferably 0.001 to 0.05 parts by mass, and more preferably 0.001 to 0.02 parts by mass, per 100 parts by mass of the component (A).
[0060] 2. Manufacturing method of the cured product As described above, the cured product can be obtained by heating and curing the addition curing silicone rubber composition. In this embodiment, the addition curing silicone rubber composition is molded and annealed to obtain the cured product, and the heating conditions (heating temperature, heating time) in the molding and annealing steps can be adjusted so that the area ratio of the above-mentioned peak B satisfies the above range.
[0061] The molding method is not particularly limited, and examples thereof include injection molding and press molding. For example, in the case of press molding, the silicone rubber composition is poured into a mold, pressurized and heated under predetermined conditions, and then annealed in an incubator or the like. By adjusting the heating conditions (heating temperature, heating time) in the molding step and the annealing step, the area ratio of peak B in the NMR spectrum of the obtained cured product can be adjusted. In particular, it is preferable to make the heating conditions in the annealing step milder than the conventional general conditions, and for example, when curing at 80 to 160°C, it is preferable to make the heating time shorter than the conventional general conditions (for example, less than 1 hour, preferably 45 minutes or less, more preferably 30 minutes or less).
[0062] The obtained cured product has a transmittance of 70% or more, more preferably 80% or more, even more preferably 85% or more, and most preferably 88% or more, of light having a wavelength of 265 nm measured by an ultraviolet-visible near-infrared spectrophotometer when cut into a 1 mm thick plate. In addition, the transmittance of light having a central wavelength of 265 nm after irradiation with light having a central wavelength of 265 nm from a position 1 mm away from a UVC-LED light source for 400 hours is preferably 88% or more. A cured product having such a light transmittance can be suitably used as an optical component.
[0063] 3.Applications The cured product has good durability against ultraviolet rays. Therefore, the cured product is suitable as an optical component, particularly an optical component used in an ultraviolet irradiation device using a light source that emits ultraviolet rays. The type of optical component used in the ultraviolet irradiation device is not particularly limited, and may be, for example, a sealing member, an adhesive member, a transparent member that transmits ultraviolet rays, or a light flux control member that controls the light distribution of ultraviolet rays.
[0064] An ultraviolet irradiation device according to one embodiment of the present invention will be described below.
[0065] FIG. 1 is a schematic diagram showing an ultraviolet irradiation device 100 of the present embodiment. 1, the ultraviolet irradiation device 100 includes a substrate 110, a light source 120 that emits ultraviolet light, an ultraviolet-transmitting window member 130, and a resin adhesive layer 140. The ultraviolet-transmitting window member 130 and the resin adhesive layer 140 are optical components used in the ultraviolet irradiation device, and at least one of them contains the above-mentioned cured product.
[0066] The type of the substrate 110 is not particularly limited, but may be, for example, a multi-layer substrate such as a low-temperature co-fired ceramic (LTCC) substrate or a high-temperature co-fired ceramic (HTCC) substrate. In this embodiment, the substrate 110 has a recess 110a that houses a light source 120 that emits ultraviolet light.
[0067] The light source 120 that emits ultraviolet light is mounted on the substrate 110. In this embodiment, the light source 120 is disposed in the recess 110a. The light source 120 that emits ultraviolet light is not particularly limited as long as it emits ultraviolet light, and examples thereof include a light-emitting diode (LED), a mercury lamp, a metal halide lamp, a xenon lamp, and a laser diode (LD). In this embodiment, the light source 120 is a light-emitting element such as a light-emitting diode (LED). The central wavelength of the ultraviolet light emitted from the light source 120 is preferably 200 to 350 nm, and more preferably 240 to 300 nm from the viewpoint that the desired effects such as sterilization efficiency are particularly easily obtained. In other words, the ultraviolet light is more preferably ultraviolet C wave (UVC).
[0068] The ultraviolet ray transmitting window member 130 is a member that transmits ultraviolet rays emitted from the light source 120. In this embodiment, the ultraviolet ray transmitting window member 130 is disposed so as to cover the recess 110a of the substrate 110 and to face the light emitting surface of the light source 120 in the recess 110a (see FIG. 1). The material of the ultraviolet ray transmitting window member 130 may be any material that transmits ultraviolet rays (particularly deep ultraviolet rays), and may be the above-mentioned cured product, or may be quartz glass, sapphire, MgO, MgF2, CaF2, synthetic phased silica, or the like.
[0069] The resin adhesive layer 140 may be a sealing member disposed between the substrate 110 and the ultraviolet ray transmitting window member 130. In this embodiment, the material of the resin adhesive layer 140 is not particularly limited, and may be the above-mentioned cured product, an acrylic resin, an epoxy resin, a silicone resin, an organic / inorganic (e.g., silicone / silica) hybrid resin, a fluorine resin, or the like.
[0070] The distance d between the ultraviolet ray transmitting window member 130 and the light emitting surface of the light source 120 on the optical axis LA of the light source 120 is not particularly limited, but may be, for example, 0.1 to 10 mm, and preferably 0.5 to 5 mm (see FIG. 1). Here, the "optical axis LA of the light source 120" refers to the central light ray of the three-dimensional emitted light flux from the light source 120.
[0071] According to the ultraviolet irradiation device 100 according to the above embodiment, at least one of the ultraviolet transmissive window member 130 and the resin adhesive layer 140 contains the above cured material. Therefore, these optical components are less likely to deteriorate even when irradiated with ultraviolet light (e.g., UVC) for a long period of time.
[0072] 1 is shown as an ultraviolet irradiation device in the above embodiment, but the present invention is not limited to this and may be any device having a light source that emits ultraviolet rays. In other words, the optical components for the ultraviolet irradiation device are not limited to the ultraviolet transmission window member 130 and the resin adhesive layer 140, but may be any components that are required to suppress deterioration such as discoloration due to ultraviolet rays.
[0073] For example, the cured product may be used as an optical control member for controlling the distribution of ultraviolet light. Such an optical control member may be any of a condenser lens, a diffusing lens, a total reflection lens, and a hemispherical lens for controlling the distribution of ultraviolet light emitted from a light source.
[0074] Figures 2A and 2B are diagrams showing an ultraviolet irradiation device 100 according to another embodiment. Figure 2A is a plan view, and Figure 2B is a cross-sectional view taken along line BB in Figure 2A. Note that the same reference numerals are used to designate the same or similar members as those in Figure 1, and detailed descriptions thereof will be omitted.
[0075] As shown in FIG. 2B, ultraviolet irradiation device 100 has substrate 110, light source 120 that emits ultraviolet light, and light flux controlling member 230 (optical component) arranged on light source 120.
[0076] Light flux controlling member 230 is a member that controls the light distribution of ultraviolet light emitted from light source 120 that emits ultraviolet light, and is arranged facing the light emitting surface of light source 120 (see FIG. 2B ). Light flux controlling member 230 has incident surface 231 and exit surface 232. In the present embodiment, incident surface 231 and exit surface 232 are rotationally symmetric with respect to central axis CA of light flux controlling member 230. Light flux controlling member 230 can be arranged on light source 120 such that central axis CA of light flux controlling member 230 coincides with optical axis LA of light source 120. Distance d between incident surface 231 and the light emitting surface of light source 120 on optical axis LA of light source 120 can also be similar to that described above.
[0077] In this way, an optical component including a cured product of the silicone rubber composition is also suitable as an optical control member for controlling the distribution of ultraviolet light in the ultraviolet irradiation device 100.
[0078] The above-mentioned ultraviolet irradiation device, particularly the deep ultraviolet light emitting device, can be widely used for various applications, such as water sterilization and purification devices for water purifiers, water coolers, water servers, medical pure water, humidifiers, dishwashers, dental chairs, etc. EXAMPLES
[0079] The present invention will be further described below with reference to examples and comparative examples, but the technical scope of the present invention is not limited thereto.
[0080] <Examples 1 to 3 and Comparative Example 1> (1) Preparation of addition-curable silicone rubber composition As an addition-curing silicone rubber composition, Silopren LSR7060 manufactured by Momentive Performance Materials, Inc. (a silicone rubber composition containing an organopolysiloxane having an average composition represented by formula (1), an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms per molecule, and a curing catalyst) was prepared.
[0081] (2) Preparation of test specimens The silicone rubber composition was placed in a mold and cured, and then further post-cured in a thermostatic oven to prepare a disk-shaped test piece of the cured silicone rubber composition, having a thickness of 1 mm and a diameter of 30 mm. The mold temperature and the heating temperature and heating time in the thermostatic oven were as described below. 13 The ratio of the area of peak B to the total area of peak A appearing at 18.0 to 18.5 ppm and the area of peak B appearing at 9.0 to 10.0 ppm in the C-MAS-NMR spectrum was adjusted to the value shown in Table 1. Specifically, the resin was heated in a mold at 120°C for 1 minute, and then heated in an incubator at 140°C for curing. In Comparative Example 1, no heating was performed in the incubator, and in Comparative Example 2, the heating time in the incubator was 60 minutes, and in Examples 1 to 4, the heating time was between that of Comparative Example 1 and Comparative Example 2.
[0082] (3)Analysis (3.1) NMR measurement (Pretreatment) The central portion of the test piece was taken and cut into 0.5 to 1.0 mm squares.
[0083] (measurement) Under the following conditions 13 C-MAS-NMR measurements were performed. (Measurement conditions) Equipment: Nuclear magnetic resonance Varian VNMRS-400 Observation kernel: 13 C Observation frequency: 100.5MHz Measurement method: DDMAS Reference material: Adamantane Pulse width: 2.7μsec Waiting time: 15sec Number of times: 5800 Rotation frequency (MAS rotation speed): 15kHz Sample temperature: 23℃ NMR data processing, such as calculation of peak areas, was performed using Delta v6.0 manufactured by JEOL. Baseline correction was performed using the "Base Correct" function (automatic baseline correction) of the same software.
[0084] (3.2) ATR-FTIR Measurement The surface of the center of the test piece was subjected to ATR-FTIR measurement under the following conditions to obtain an absorption spectrum. (Measurement conditions) Equipment: Fourier transform infrared spectrophotometer (Agilent Cary 620 FTIR, manufactured by Agilent Technologies) Measurement method: Microscopic ATR method ATR prism: Germanium (spherical) refractive index 4.0 Incident angle: 30° Measurement area: 650~4000cm -1 Detector: MCT, High Sensitivity 100μm Reflection count: 1 Resolution: 4cm -1 Number of times accumulated: 128 times
[0085] The background measurement was performed in the same manner, except that the sample was not brought into contact with the prism. In the ATR method, the intensity of the absorption spectrum obtained by the measurement changes depending on the degree of contact between the sample and the ATR prism, so the measurement was performed so that the maximum peak intensity was 0.33 to 0.34.
[0086] (analysis) In the obtained absorption spectrum, 1350 cm -1 and 926cm -1 were defined as the left and right origins of the baseline, respectively. And 1013 cm -1 The height of the peak due to the Si-O bond near h ref was calculated. Also, 2193cm -1 and 2080cm -1 are defined as the left and right starting points of the baseline, respectively, and 2138 cm -1 The peak height h due to the hydrosilyl group in the vicinity SiH was calculated. The obtained value was then substituted into the following formula to calculate the concentration of hydrosilyl groups (SiH concentration). SiH concentration [mmol / g] = 30.2 × h SiH / h ref +0.021
[0087] (4) UV irradiation test (Fabrication of light-emitting device) Using the obtained test piece, a light-emitting device shown in Fig. 3 was produced. Specifically, a UVC-LED light source was placed at the bottom of a container as light source 1 for emitting ultraviolet light, and the opening of the container was blocked with test piece 2 to produce a light-emitting device. Light source 1: UVC-LED light source (KL265-50W-SM-WD, Crystal IS). Note that it is driven at a constant current of 350 mA, and the illuminance measured at 10 mm directly above light source 1 by a UV illuminometer is 20 mW / cm. 2 That's all. Distance d between the light emitting surface of the light source 1 and the test piece 2: 1 mm
[0088] (UV irradiation test) Then, light with a central wavelength of 267 nm was irradiated from light source 1 (UVC-LED light source), and the irradiation time during which the light transmittance of 88% or more at a wavelength of 265 nm was maintained was determined. The light transmittance was measured using an ultraviolet-visible-near infrared spectrophotometer in an area having a diameter of 2 mm and centered on the optical axis directly above the light source 1.
[0089] The evaluation results of Examples 1 to 4 and Comparative Examples 1 and 2 are shown in Table 1. 13 The main part of the C-MAS-NMR spectrum is shown in Figure 4. Furthermore, the ATR-FTIR absorption spectra of Examples 1 to 4 are shown in Figures 5A and 5B.
[0090] [Table 1]
[0091] As shown in Table 1, 13 In the test pieces of Examples 1 to 4, in which the ratio of the area of peak B to the sum of the area of peak A appearing at 18.0 to 18.5 ppm and the area of peak B appearing at 9.0 to 10.0 ppm in the C-MAS-NMR spectrum was 31% or more and 68% or less, the irradiation time during which the light transmittance at a wavelength of 265 nm was maintained at 88% or more was 400 hours or more. In contrast, the test piece of Comparative Example 2 in which the area ratio of peak B was higher than 68% or the test piece of Comparative Example 1 in which the area ratio was lower than 31% required an irradiation time of shorter than 400 hours to maintain a light transmittance of 88% or higher at a wavelength of 265 nm. From these, it can be seen that when the ratio of the area of peak B is 31% or more and 68% or less, degradation due to deep ultraviolet light is small and the durability is high.
[0092] Furthermore, by comparing Examples 1 to 4 with Comparative Examples 1 and 2, it was found that the test pieces in which the concentration of hydrosilyl groups in the cured product was 0.20 mmol / g or more and 0.54 mmol / g or less, for which the absorption spectrum in ATR-FTIR was obtained, maintained a light transmittance of 88% or more at a wavelength of 265 nm for 400 hours or more of irradiation time. In contrast, the test piece of Comparative Example 2, in which the concentration of hydrosilyl groups in the cured product was lower than 0.20 mmol / g, and the test piece of Comparative Example 1, in which the concentration was higher than 0.54 mmol / g, required an irradiation time of less than 400 hours to maintain a light transmittance of 88% or more at a wavelength of 265 nm. These findings also show that when the concentration of hydrosilyl groups in the cured product is 0.20 mmol / g or more and 0.54 mmol / g or less, degradation due to deep ultraviolet light is minimal and the product has high durability.
[0093] Furthermore, in the test pieces of Examples 1 to 4, the peak derived from the vinyl group, which is required for the absorption spectrum in ATR-FTIR, was not detectable, and it was found that the concentration of the vinyl group was lower than that of the test piece of Comparative Example 1. This shows that the test pieces of Examples 1 to 4 were less yellowed than the test piece of Comparative Example 1, and were less deteriorated by deep ultraviolet rays. [Industrial Applicability]
[0094] The cured product of the present invention is less deteriorated by irradiation with deep ultraviolet light and has durability. Therefore, the cured product can be suitably used, for example, as an optical component of an ultraviolet irradiation device that irradiates ultraviolet light, particularly UVC light. [Explanation of symbols]
[0095] 1 light source 2. Test specimens 100 Ultraviolet irradiation device 110 Substrate 120 Light source that emits ultraviolet light 130 UV-transmitting window material 140 Resin adhesive layer 230 Light flux control member 231 Incidence plane 232 Exit surface
Claims
1. A cured product of an addition-curable silicone rubber composition, 13 In a C-MAS-NMR spectrum, the ratio of the area of peak B to the total area of peak A appearing at 18.0 to 18.5 ppm and the area of peak B appearing at 9.0 to 10.0 ppm is 31% or more and 68% or less. cured product.
2. A cured product of an addition-curable silicone rubber composition, In the ATR-FTIR absorption spectrum, 2120 to 2180 cm -1 the concentration of hydrosilyl groups in the cured product calculated from a peak derived from hydrosilyl groups appearing in the cured product.
3. In the ATR-FTIR absorption spectrum, 1630 to 1670 cm -1 The peak due to the vinyl group that appears in the The cured product according to claim 1 or 2.
4. The addition curable silicone rubber composition comprises: (A) an organopolysiloxane having an average composition represented by formula (1), Formula (1): R 1 a SiO (4-a)/2 (In the formula, R 1 is an alkenyl group, an alkyl group having 1 to 6 carbon atoms, a fluorinated alkyl group having 1 to 6 carbon atoms, an aryl group, or a cycloalkyl group having 5 to 12 carbon atoms, and R 1 at least two of the groups are alkenyl groups, and a is a positive number of 1.95 to 2.
05. (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in each molecule, and (C) Curing catalyst Including, The cured product according to claim 1 or 2.
5. The cured product according to claim 1 or 2 is included. Optical components for ultraviolet irradiation equipment.
Citation Information
Patent Citations
Isocyanuric ring-containing polysiloxane with terminal hydrogen
JP2010265374A
Method for curing silicone resin composition
JP2012121960A
Method of forming cured thin film using photocurable silicone resin composition
JP2013063391A
Transparent liquid silicone rubber composition, and cured product
JP2021031543A
Method for preventing addition reaction inhibition of addition curable silicone
JP2021195395A